Poverty and Plenty in Scandinavia and the North Atlantic : Later Historical Archaeologies of Material Excess and Scarcity (Bloomsbury Publishing Plc., 2025)
Examining the archaeological material of the modern period, over a period of the last 500 years, this open access book presents a series of case studies that challenges the fallacy of Nordic egalitarianism. The widening gap between rich and poor Western countries is now a well-known phenomenon and, while Scandinavia has often been hailed as one of the regions where inequality has been the lowest, even here a similar trend toward widening inequality has been observed. The topic of inequality has long been a major focus of interest within archaeology, but the goal and novelty of this volume is to start with the problem of material disparity by asking what this means, rather than starting with the problem of social inequality and trying to map observable material disparities onto its various conceptualizations. Key themes include variations between urban and rural contexts, as well as geographical proximity to centres of commerce and industry, different local/cultural valuations of – especially consumer – goods and discard practices. The result is an original study of a wealth of material culture that tells us how extensive this inequality actually was and the different ways it appeared in various societies. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the University of Iceland. This volume brings together the research of multiple scholars working in historical archaeology and history in the Nordic countries, to explore the issue of inequality and material disparity. The papers offer a broad and diverse range of case studies from the high to low, urban to rural; it includes places, sites and assemblages from Finland, Sweden, Norway, Denmark and Iceland as well as broader reflections within the Atlantic world; and it deals with time periods from the 16th to early 20th century. As a whole, the volume offers an exceptional cross-section of contemporary, innovative and inspiring research projects within Scandinavia and the North Atlantic.
Keywords: inequality; poverty; historical archaeology; Scandinavia